2006
DOI: 10.1369/jhc.5a6799.2006
|View full text |Cite
|
Sign up to set email alerts
|

Method of Specific Detection of Apoptosis Using Formamide-induced DNA Denaturation Assay

Abstract: S U M M A R Y We compared the reliability between apoptosis detection methods, namely, the terminal deoxynucleotidyl transferase-mediated dUTP-digoxigenin nick end labeling (TUNEL) method and formamide-induced DNA denaturation assay using a monoclonal antibody (MAb) to single-stranded DNA (ssDNA) (formamide-MAb assay). Reaction targets in these methods are different: the TUNEL method recognizes free 39-OH DNA ends, whereas the formamide-MAb assay detects ssDNA itself (25-30 bp). We found that the formamideMAb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
2

Year Published

2007
2007
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 38 publications
2
26
2
Order By: Relevance
“…Because TUNEL detects internucleosomal DNA fragmentation, which is one of the hallmarks of apoptosis, this correlation supports specific binding of the tracer to target apoptotic cells. However, we cannot rule out the possibility that, in addition to uptake by apoptotic cells, 18 F-ML-10 also accumulated in cells manifesting features of necrotic cell death, because positive TUNEL staining has been reported in such cells as well (18)(19)(20). As shown in the present study, 3 H-ML-10 accumulated in apoptotic cells but not in cells undergoing necrosis in vitro ( Table 1).…”
Section: Discussioncontrasting
confidence: 49%
“…Because TUNEL detects internucleosomal DNA fragmentation, which is one of the hallmarks of apoptosis, this correlation supports specific binding of the tracer to target apoptotic cells. However, we cannot rule out the possibility that, in addition to uptake by apoptotic cells, 18 F-ML-10 also accumulated in cells manifesting features of necrotic cell death, because positive TUNEL staining has been reported in such cells as well (18)(19)(20). As shown in the present study, 3 H-ML-10 accumulated in apoptotic cells but not in cells undergoing necrosis in vitro ( Table 1).…”
Section: Discussioncontrasting
confidence: 49%
“…This conclusion is in disagreement with the data reported in several earlier studies (2)(3)(4)(5)(6)(7).…”
contrasting
confidence: 97%
“…Under these conditions, the MAb detects DNA damage associated with apoptotic chromatin condensation per se, but does not detect presence of DNA breaks that require more intense denaturation (2,14). Electron microscopic studies confirmed this conclusion (6). For sensitive detection of druginduced DNA breaks, more intense denaturation is needed.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…ssDNA was stained in vivo to verify the amount of apoptosis in meningiomas, as the antibody only stains singlestranded apoptotic DNA but not necrotic cells (38)(39)(40), however no significant inverse correlation with Smac/ DIABLO or surviving expression has been seen as previously shown in glioblastomas as well (31,41 (42). Tumor cells with reduced Smac resist apoptosis leading to the suggestion for an obligatory role for Smac/DIABLO in these tumor cells during several pathways of apoptosis induction (43).…”
Section: Discussionmentioning
confidence: 94%